2019
DOI: 10.1016/j.jaci.2018.12.975
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of a Novel Peptide-Based Immunotherapy for Peanut Allergy

Abstract: RATIONALE: Peanut allergy is a life-threatening condition for which there is currently no cure. Immunotherapy using whole peanut preparations is hindered by risk of causing severe allergic reactions during treatment. PVX108 is a peptide-based immunotherapy being developed to treat peanut allergy without triggering allergic reactions during treatment. METHODS: PVX108 comprises a mixture of short, synthetic peptides derived from sequences of major peanut allergens, formulated for intradermal injection. Basophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, the efficacy of desensitization is lower, particularly for EPIT. Peptide immunotherapy is another approach to minimize AEs by replacing whole allergens with short allergen peptides, which have a reduced capacity to crosslink IgE on the surface of mast cells and basophils ( 63 , 64 ). Preliminary findings from a clinical trial for PN allergy demonstrated no serious AEs ( 63 ).…”
Section: Current and Investigative Treatments For Food Allergymentioning
confidence: 99%
“…However, the efficacy of desensitization is lower, particularly for EPIT. Peptide immunotherapy is another approach to minimize AEs by replacing whole allergens with short allergen peptides, which have a reduced capacity to crosslink IgE on the surface of mast cells and basophils ( 63 , 64 ). Preliminary findings from a clinical trial for PN allergy demonstrated no serious AEs ( 63 ).…”
Section: Current and Investigative Treatments For Food Allergymentioning
confidence: 99%
“…IL-4, IL-5, IL-31) thought to be implicated in control of those levels and other cell populations (eosinophils/basophils) implicated in allergic disease [2933]. In addition, concerted efforts have ben made to improve the efficacy of allergen-induced attenuation of responses [7, 912, 1518]. We have previously reported on the use of a novel therapy, aimed at manipulating self-reactive immune regulatory networks through deliberate perturbation of idiotype: anti-idiotype interactions, as a potential mechanism to attenuate several pathological immune reactions in rodents, including allergic sensitization to ovalbumin [19].…”
Section: Discussionmentioning
confidence: 99%
“…1b). It is worth stressing at this stage that the therapy used is one which occurs through mechanisms independent of the antigen used for sensitization, a feature of significant importance clinically when often the allergen cannot be identified and/or synthesized for allergen-specific desensitization [1518].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small Phase I study in Australia of 66 participants who underwent intradermal injection with a product consisting of several synthetic peptides derived from peanut allergens (PVX108; Aravax, Melbourne, Australia), the decreased allergenicity of peptide immunotherapy was demonstrated by a lack of basophil activation to the immunotherapy. 18 During the study, there were no serious adverse events and the AEs that did occur were mostly self-resolving injection site reactions. Although the study was limited by small sample size, the results indicated that peptide immunotherapy may prove advantageous in regards to reducing adverse reactions that may otherwise preclude use by an allergic individual.…”
Section: Future Directionsmentioning
confidence: 91%